Partisan‐Motivated Evaluations of Sexual Misconduct and the Mitigating Role of the #MeToo Movement. Issue 4 (8th July 2021) - Klar, Samara; McCoy, Alexandra
Abstract: When individuals evaluate something as serious as sexual misconduct allegations in politics, they are often motivated to defend their party—but outside forces can reduce these partisan biases. We bridge work from political psychology with studies of social movements to theorize how the #MeToo movement helps to mitigate partisan‐motivated evaluations of sexual misconduct. With a two‐wave survey experiment, we find that partisans are more likely to view out‐party members as guilty of sexual misconduct and that individuals less likely to reflect are particularly biased in their evaluations. We then turn to the #MeToo movement and its potential to promote reflection. We show that support for #MeToo is associated with more evenhanded evaluations of sexual misconduct in politics, particularly among those unlikely to reflect on their own. This study contributes to our broader understanding of how movements can induce reflection and moderate partisan‐motivated reasoning among the mass public.